Towards a fragment approach to haemozoin inhibiting antimalarials : exploration of coordination and π-stacking interactions with Fe(III)PPIX by spectroscopy and synthesis - Kuter, David (Department of Chemistry, 2014)
Includes bibliographical references (leaves 116-122).